2015
DOI: 10.15226/jnhfs.2015.00151
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Uniform Biomarker Signature in Calves Heart and Lung to Detect the Abuse of Different Anabolic Substances

Abstract: Anabolic agents like steroid hormones or β-agonists are used in food-producing animals in order to increase muscle mass and reduce fat content [1,2]. The application of specific anabolic agents in animal husbandry is allowed and common in different countries, e.g. USA, Canada, South Africa, etc. Due to proven side effects of substance residues for the consumer, the use of all growth promoting agents is forbidden within the European Union (EU)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…In addition, body fat percentage, total and HDL cholesterol had interactional effects on the triglycerides and waist circumference. These results are in line with those of previous studies, which have found that risk factors for cardiovascular diseases tend to accumulate [16][17][18][19][20][21][22]. It has also been shown that unhealthy lifestyle behaviors (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, body fat percentage, total and HDL cholesterol had interactional effects on the triglycerides and waist circumference. These results are in line with those of previous studies, which have found that risk factors for cardiovascular diseases tend to accumulate [16][17][18][19][20][21][22]. It has also been shown that unhealthy lifestyle behaviors (e.g.…”
Section: Discussionsupporting
confidence: 93%